Robust supramolecular composite hydrogels for sustainable and "visible" agriculture irrigation. Issue 43 (27th October 2021) - Ding, Chenfeng; Zhang, Shuai; Fu, Xuewei; Liu, Tuan; Shao, Lin; Fei, Mingen; Hao, Cheng; Liu, Yuan; Zhong, Wei-Hong
Abstract : To combat severe soil desertification and sandstorms, the application of appropriate hydrogels to dry land/desert is a promising solution to advance sustainable water irrigation and retention, and even realize "intelligent" agriculture. Abstract : To combat severe soil desertification and sandstorms, the application of appropriate hydrogels to dry land/desert is a promising solution to advance sustainable water irrigation and retention, and even realize "intelligent" agriculture. To this end, the development of a hydrogel with stable monitoring functions and good mechanical properties to maintain the swelling capability under soil would be significant for "intelligent" agriculture applications. Herein, we report a robust bio-based hydrogel with excellent mechanical properties and unique fluorescence performance for monitoring irrigation applications. This bio-hydrogel possesses a double cross-linked interpenetrating supramolecular network in a bacterial cellulose (BC) porous matrix, which provides its high tensile/compressive strength (∼0.96/1.3 MPa) and excellent Young's modulus (∼6.67 MPa, vs. 0.01–1.0 MPa for reported agricultural hydrogels), as well as high strength retention after experiencing repeated swelling/drying and long-term compressive processes. Furthermore, the hydrogel displays unique non-traditional fluorescence with excellent stability even under extreme environmental conditions, such as high/low temperature and various organic solvents. The excellent fluorescence characteristics offer the potential to realize "visualized" agricultural irrigation. This study not only provides a distinctive bio-based hydrogel with broadened applications, but also presents new insight to promote the development of sustainable agriculture.